#TITLE_ALTERNATIVE# - I.P. (NIM 123 02 013), Baharianto
Abstract : One of many methods to estimate hydrocarbon reserve is subsurface geological structure modeling. In this research writer used gravity method which measuring the gravity field variation caused by densities variation among the rocks. Negative anomaly analysis and spectral analysis are used to reduce the ambiguity of subsurface modeling, Second horizontal derivative analysis used to analyze negative anomaly caused by geological structures down below. Negative anomaly caused by sedimentary basin is very important structure since sedimentary basin is potential for hydrocarbon reserve. While spectral analysis generates the depth estimation that caused by the source of anomaly which help the two dimensions forward modeling. Software Grav2DC are used to make the two dimensional forward modeling. Forward modeling generates that South Luwuk area has possibility containing hydrocarbon reserve. The negative anomaly caused by the same sedimentary basin. This East-West sedimentary basin can be seen by observing the pattern of negative anomaly in the contoured anomaly Bouguer map.